Impact of early COVID-19 pandemic on the US and European stock markets and volatility forecasting - Mohammad Abedin (Economic Research-Ekonomska Istraživanja, 2022)
This study examines the impact of early COVID-19 pandemic on U.S. and European stock indices, implied volatility (IV) indices, and forecasting accuracy of IV indices from daily data of January 2012 to December 2020, using an out-of-sample assessment of COVID-19. Our results show that COVID-19 death and recovery cases have had a significant positive impact on S&P 500, DJIA and NASDAQ 100. On the other hand, VIX, VXD and VXN show a negative association. Again, we also observe the significant impact of COVID-19 on stock trading prices and volatility expectations. Furthermore, the evidence of the point forecasts is more reliable for European IV indices than for U.S. IV indices. Finally, this study validates the informational efficiency of IV indices on the financial markets and has implications for investors regarding portfolio management and investment risk minimisation in similar future pandemic situations.